Potential mechanisms of Lian-Zhi-Fan solution for TNBS-induced ulcerative colitis in rats via a metabolomics approach - Bai, Junyi; Xiong, Tingting; Wang, Xiao; Cheng, Yanfen; Luo, Ruifeng; Yang, Xiangdong; Fu, Chaomei (Frontiers in Pharmacology, 2022)
Lian-zhi-fan (LZF) decocotion is a traditional Chinese medicine botanical drug hospital prescription prepared by the fermentation of decoction of Coptidis Rhizome (Huanglian), Gardeniae Fructus (Zhizi) and Alum (Baifan). It has been used clinically for the treatment of anal fistula, perianal abscess, ulcerative colitis (UC) and other anorectal diseases in China for hundreds of years. However, due to the complexity of traditional Chinese medicine, the potential mechanisms of LZF in the treatment of UC were still unknown. In this study, the remarkable pharmacological effects of LZF on TNBS-induced UC rats were primarily investigated. To explore the complex targets and regulatory mechanisms of metabolic networks under LZF intervention, a metabolomics approach mediated by HPLC/Q-TOF-MS analysis was used to screen the different metabolites and belonging metabolic pathways in the serum, so as to characterize the possible anti-UC mechanisms of LZF. After consecutive rectal administration of LZF for 7 days, the significant amelioration effects on the body weight loss, the DAI score, colon inflammation in UC rats could be found. Based on it, further metabolomics identified 14 potential biomarkers in the treatment of UC with LZF, in which 5 biomarkers possessed diagnostic significance, namely L-alanine, taurocholic acid, Niacinamide, cholic acid, and L-valine. These metabolites were mainly involved in 12 metabolic pathways, including nicotate and nicotinamide metabolism, glycospholipid metabolism, arginine and proline metabolism, primary bill acid biosynthesis, pantothenate and COA biosynthesis. Therefore, these metabolomics pathways suggested that LZF ameliorated UC by regulating amino acid metabolism, fat metabolism and energy production. This study provided a useful approach to explore the potential mechanism of herbal prescription in UC treatment mediated by metabolomics.